Effects of dynamic variables on industrial output in one of the world's fastest-growing countries: Case evidence from India - A. Sankaran; A. Vadivel; M. Abdul Jamal (Future Business Journal, 2020)
Increase in industrial output is an important indicator to identify the socio-economic development of a nation. India is one of the fastest-growing economies in the world; using its comparative advantage and capitalizing its educated youths, it tries to be as a hub of manufacturing in the world map. Under these circumstances, the present study attempts to identify the effects of dynamic macroeconomic variables on manufacturing output in India using second-ary data from 1990Q1 to 2017Q4 sourced from the World Bank, and IMF, RBI, ASI and published materials are other source of information. This study considered variables such as industrial production, population, agricultural output, exchange rate, export, oil price, and gross fixed capital formation. We employed ADF and PP unit root tests, Johansen co-integration test, and error correction model based on Granger causality test. This study found that manufactur-ing output was driven by agricultural output, export and population. The chief role played by the agricultural output in affecting the manufacturing output suggested that the agricultural sector is still serving as engine of economic development in general and manufacturing output in particular in the case of fast-growing Indian economy. Further, investment on education, health, trainings and other capacity building in the form of human capital on population will lead the industrial sector to get strengthened through observing entrepreneurial spirit, high skilled labours, tech-nicians, and managers. Finally, it is suggested that the superior focus on tapping the potential market on the planet, research and development, mechanization, proper quality control, skill development, better management, and effec-tive marketing will give a new life to the manufacturing sector of the fast-growing Indian economy.
Keywords: O11; E20 C220; E220; F430; 650; Causality; Indian industries; Long-run relationship; Manufacturing output; New industrial policy